Analysis on Value Perception, Word of Mouth, Price, and Trust towards Patient Loyalty at Proklamasi Hospital, Jakarta - Carolina Carolina; Endang Ruswanti; Rian Adi Pamungkas (Penerbit Kemala Indonesia, 2021)
The decrease upon return visits in hospital becomes an indicator of patient loyalty. Thus, in this study aimed to obtain correlation on value perception, word of mouth, price and trust towards patient loyalty at Proklamasi hospital, Jakarta. The several variables such as value perception, word of mouth, price, trust and loyalty are performed in this study. The population of this study taken from ongoing patients at Proklamasi hospital, Jakarta. In addition, the samples observation of this research are 200 respondents using Hair method. This study also uses a cross-sectional study design to obtain correlation between dependent and independent variables with. path analysis test. The results show a determinant value of covariance matrix can be achieved. Around 1208.180 (positive results and greater than 0.000). thus, in this study we find that no multicollinearity while, the measurement model test by using Chi-square method is 0,000 (the value is small so that the simultaneous test is accepted). In addition, if the degree of freedom is 0 it’s indicates that the first hypothesis (H1) is accepted. Thus, the positive correlation on value perception, word of mouth, and trust towards patient loyalty. On the contrary, price has no effect on patient loyalty. Furthermore, word of mouth has the greatest influential value of all. Value perception, word of mouth, and price can directly increase patient loyalty without being influenced by trust.